Biodiversity patterns of epifaunal assemblages associated with the gorgonians Eunicella gazella and Leptogorgia lusitanica in response to host, space and time - Carvalho, S. (2014)
Patterns of biodiversity (α- and β-diversity), abundance and community structure of the epifaunal assemblages associated with two gorgonians, Eunicella gazella and Leptogorgia lusitanica, were analysed in relation to host, colony size, location and time. Colony size and time were the major factors shaping attendant assemblages. Patterns of α-diversity and β-diversity were host-dependent. Assemblages associated with E. gazella showed a significant inter-annual variability for most of the metrics analysed, while in those associated with L. lusitanica only Shannon–Wiener varied significantly between years. In L. lusitanica Hurlbert's expected number of taxa was significantly lower in small-sized than in medium- to large-sized colonies, but an opposite pattern was detected for β-diversity, reflecting the higher heterogeneity among small-sized colonies. The dbRDA analysis segregated the assemblages associated with each of the two hosts; the faunal patterns were mainly explained by colony size related attributes (area, number of branches and, to a lesser extent, width) and the “colonial” epibiont cover. However, we suggest that altogether they may act as a metacommunity, with high temporal and spatial fluidity in their composition and structure related to multiple factors including not only a component of stochasticity but also life history events, biotic interactions and response to habitat heterogeneity and environmental variability.